Muscle glycogen breakdown and lactate metabolism during intensive exercise in Thoroughbred horses - Kitaoka, Y.; Endo, Y.; Mukai, K.; Aida, H.; Hiraga, A.; Hatta, H. (The Journal of Physical Fitness and Sports Medicine, 2014)
We examined the muscle glycogen, and muscle and plasma lactate concentrations before and after 1 and 2 min of intensive exercise at 120% VO2max, and examined possible relationships between these indexes and protein levels of monocarboxylate transporters (MCT) in the gluteus medius muscle of Thoroughbred horses. The horses underwent 1 and 2 min of intensive exercise at the speed of 120% maximal oxygen consumption (VO2max) on a treadmill. The plasma lactate concentration increased after 1-min exercise (11.7 ± 0.8 mmol/L) and 2-min exercise (23.1 ± 1.1 mmol/L). The muscle lactate concentration increased after 1-min exercise (17.3 ± 2.1 mmol/kg) and 2-min exercise (23.6 ± 2.0 mmol/kg). While there was no significant difference in lactate accumulation in the plasma between the first minute and the second minute, lactate accumulation in muscle significantly decreased in the second minute compared with the first minute. The muscle glycogen level decreased after both 1- (42%) and 2-min (41%) exercise, but there was no difference between the levels after 1- and 2-min exercise. The muscle lactate concentration after 2-min intensive exercise positively correlated with the protein level of MCT4 (r = 0.78, p < 0.01). These results suggest that glycogen breakdown occurs in the first minute of intensive exercise, and Thoroughbred horses with higher muscle lactate production during exercise are endowed with higher expression of MCT4, that facilitates the efflux of lactate from muscle cells